The Search for Diversity in Baltic (E)migrant Picture Books and Fairy Tales for Children - Adomavičienė, Laimutė (Respectus Philologicus, 2026)
This article analyses Baltic (e)migrant literature for children published between 2014 and 2020, with a particular focus on how diversity is represented in picture books and fairy tales. The study examines several dimensions of diversity, including racial identity (L. Mumgaudytė’s The Day of Mr. Chao (Pono Čao diena, 2014)), intolerance towards immigrants (U. Kestere’s The Uninvited Guests (Nekviesti svečiai, 2017)), clashes of differing opinions (The Little Hedgehog and the Giant Berry (Ežiukas ir didžioji uoga, 2020), and T. Kitsik’s The Crocodile’s Tale (Krokodilo uodega, 2019)), and children with distinctive appearance (J. Baltrukonytė’s fairy tale “The Striped Bunny” (“Dryžuota Kiškiukė”, 2016) from Cartoons (Filmukai, 2016), and E. Daciūtė’s fairy tale “Four Suns” (“Keturios saulės”) from The Bear Stories. The Dream Garden (Meškių istorijos. Svajonių sodas, 2016)). The findings indicate that a substantial proportion of Baltic (e)migrant children’s literature engages explicitly with diversity-related themes. Picture books and fairy tales, in particular, foreground questions of tolerance, racial difference, distinctive physical appearance, immigration, and identity. Overall, the analysed texts suggest a gradual shift in children’s literature from more traditionally conservative framings of race, otherness, and disability towards more liberal, inclusive perspectives, accompanied by heightened attention to identity and the ethics of social recognition.
Keywords: Baltic countries (e)migrant children's literature; diversity; tolerance; identity; stereotype